Tandem Cu-catalyzed ketenimine formation and intramolecular nucleophile capture: Synthesis of 1,2-dihydro-2-iminoquinolines from 1-(o-acetamidophenyl)propargyl alcohols - Kumar, Gadi Ranjith; Kumar, Yalla Kiran; Kant, Ruchir; Reddy, Maddi Sridhar (Beilstein Journal of Organic Chemistry, 2014)
The copper-catalyzed ketenimine formation reaction of 1-(o-acetamidophenyl)propargyl alcohols with various sulfonyl azides is found to undergo a concomitant intramolecular nucleophile attack to generate 1,2-dihydro-2-iminoquinolines after aromatization (via elimination of acetyl and hydroxy groups) and tautomerization. The reaction produces 4-substituted and 3,4-unsubstituted title compounds in moderate to good yields under mild reaction conditions.
Keywords: alkyne; azide; cycloaddition; cyclization; quinoline